2010
DOI: 10.1016/j.tripleo.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of condylar resorption in temporomandibular joint osteoarthritis

Abstract: OBJECTIVE This study was performed to determine the condylar morphological variation of osteoarthritic (OA) and asymptomatic temporomandibular joints (TMJ) and to determine its correlation with pain intensity and duration. STUDY DESIGN Three dimensional surface models of mandibular condyles were constructed from Cone-Beam CT images of 29 female patients with TMJ OA (Research Diagnostic Criteria for Temporomandibular Disorders Group III) and 36 female asymptomatic subjects. Shape Correspondence was used to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
7
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 26 publications
(25 reference statements)
5
124
7
5
Order By: Relevance
“…In these studies, shape correspondence, a 3-D surface mapping technique, was used to map the condylar morphology and its alteration in osteoarthritis. 51 Indeed, this technique showed marked differences between OA and asymptomatic condyles. Importantly, the extent of these morphological changes paralleled pain severity and duration.…”
Section: Future Directions For Use Of Cbct Imagingmentioning
confidence: 98%
See 1 more Smart Citation
“…In these studies, shape correspondence, a 3-D surface mapping technique, was used to map the condylar morphology and its alteration in osteoarthritis. 51 Indeed, this technique showed marked differences between OA and asymptomatic condyles. Importantly, the extent of these morphological changes paralleled pain severity and duration.…”
Section: Future Directions For Use Of Cbct Imagingmentioning
confidence: 98%
“…Importantly, the extent of these morphological changes paralleled pain severity and duration. 51 Such technologies hold promise to evaluate temporal changes in the joints and to identify morphological variations that may have implications for clinical management or prognosis.…”
Section: Future Directions For Use Of Cbct Imagingmentioning
confidence: 99%
“…Quantification of 3D surface models of mandibular condyles in patients with TMJ OA and in asymptomatic Dentomaxillofac Radiol, 44,20140235 birpublications.org/dmfr TMJ diagnostics using CBCT subjects revealed significant differences. 54 It was even suggested that the extent of resorptive changes paralleled pain severity and duration. In another study of the same group, it was found that 3D shape analysis measurements of data simulated 3-and 6-mm defects on the surface of 3D models of condyles had an acceptable accuracy.…”
mentioning
confidence: 99%
“…Various segmentation methods have previously been validated, and although interobserver errors in segmentation present only small differences, these errors would be added to registration errors. 32,45,47,56 The artefacts generated from restorative dentistry, movement of the patient, partial volume averaging, incorrect selection of kVp/mA and threshold settings can affect the volume image and segmentation. 48,[57][58][59][60] In the absence of artefacts, Luu et al 45 clearly described that when defining the true boundary of an object, at best, the line for this boundary will cross directly through the centre of a voxel.…”
Section: Discussionmentioning
confidence: 99%
“…Computation of corresponding points between all condyles: SPHARM-PDM software v. 1.12 (open-source, http://www.nitrc.org/projects/spharm-pdm) 32,33,36,37 was then used to compute the correspondence across 4002 surface points among all right and mirrored left condyles. These 4002 surface points and the location of their respective XYZ coordinates were optimized for each corresponding condyle mesh.…”
Section: -33mentioning
confidence: 99%